Astrocitoma pilocítico em adultos: análise de uma série brasileira - Boschetti, Gabriela [UNIFESP] (2019)
Objective: To describe a national cohort of ≥18 year-old patients with PA and compare with the available literature. Method: We retrospectively review all patients ≥18 year-old with PA from our Neuro Oncology database at the Universidade Federal de São Paulo from 1991 to 2018. We analyzed data regarding clinical presentation, location, imaging features, extent of resection, adjuvant treatments and follow-up. Results: Twenty- three patients with PA were analyzed: 60.9% male; median age 26 years (range 18 to 51). Median time between first symptom and surgery was 7.9 months (range 1 to 246) and the most frequent symptoms were headache (34.8%) and seizure (26.1%). Temporal and parietal lobes were the most common locations, 21.7% each, and gadolinium enhancement was present in 90.9% of all patients. All patients underwent surgical procedure: gross total resection in 40.9%, subtotal resection in 22.7% and biopsy in 27.3%. Three patients had no information regarding the extent of the first resection, including the one who died. Adjuvant treatment with RT was performed in one patient after gross total resection and QT in one patient after biopsy. Four patients had disease progression, two after gross total resection and two after partial. They were all alive and with stable disease at the last follow-up (October 2018). Median overall survival was not reached after a median follow-up time of 88.9 months (range 1.9 to 330.4). Conclusion: According to available literature, this is the first Brazilian series regarding pilocytic astrocytomas in adults with long-term follow up. We observed a favorable outcome as reported in recent literature reviews. The most frequent location was supratentorial region, especially temporal lobe. Although according to literature, the extent of resection remains as the most important prognostic factor in these patients, we could not detect significant relationship among location or extent of resection and progression, possibly due to the reduced number of patients. Further studies, with bigger cohorts, and molecular analyses are needed to elucidate clinical features and the optimal management of adult PA.